1998
DOI: 10.2190/9u50-tt5r-tm4u-85ex
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Use of Interactive Multimedia Courseware in the Learning of Rat Dissection

Abstract: Traditionally, students learned rat dissection through reading printed dissection guides, observing teacher demonstration, and hands-on dissection practice in a Biology laboratory. Teacher demonstration was always not very effective for a large class of students. Hands-on practice consumed a lot of rats before students could master the basic skills of rat dissection. Expenditure in terms of time and resources was high in the learning of rat dissection. To help students learn rat dissection in a more cost-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, upon careful review, only six of the studies were found to fit the criteria for review. The 11 studies that did not meet the requirements for inclusion in the extended review were eliminated because they: (a) provided only descriptions of programs (Ludlow, Foshay, & Duff, 1998); (b) were concerned primarily with evaluating groupings (Ivers & Barron, 1998) or presentations that were not self-instructional (e.g., expert systems) (McCoy, 1994), simulations (Strang, Murphy, Kauffman, Badt, & Loper, 1986) or systems change (Goldman & Barron, 1990 ;Kumar & Altschuld, 1999); (c) involved subjects other than pre-service or in-service school-based personnel (Brothen & Wambach, 1999;Ngai & Chan, 1998;Skudrna, 1997); (d) or involved training teachers or faculty to develop multimedia presentations (Fitzgerald, 1994;Fitzgerald, Hardin, & Hollingsead, 1997).…”
Section: Methods Selection Of Studiesmentioning
confidence: 99%
“…However, upon careful review, only six of the studies were found to fit the criteria for review. The 11 studies that did not meet the requirements for inclusion in the extended review were eliminated because they: (a) provided only descriptions of programs (Ludlow, Foshay, & Duff, 1998); (b) were concerned primarily with evaluating groupings (Ivers & Barron, 1998) or presentations that were not self-instructional (e.g., expert systems) (McCoy, 1994), simulations (Strang, Murphy, Kauffman, Badt, & Loper, 1986) or systems change (Goldman & Barron, 1990 ;Kumar & Altschuld, 1999); (c) involved subjects other than pre-service or in-service school-based personnel (Brothen & Wambach, 1999;Ngai & Chan, 1998;Skudrna, 1997); (d) or involved training teachers or faculty to develop multimedia presentations (Fitzgerald, 1994;Fitzgerald, Hardin, & Hollingsead, 1997).…”
Section: Methods Selection Of Studiesmentioning
confidence: 99%